Endeavor towards 2035: Selangor state structure plan - Mahamod, Lukman Hakim; Bachok, Syahriah; Ibrahim, Mansor; Zen, Irina Safitri; Abdul Hafiz, Muhammad Danial; Sophian, Nur Sofia Hanim; Md. Isa, Muhammad Hafiz Zaim (IIUM Press, 2022)
Selangor is the most developed state in Malaysia. The state thrives on the balance of progressive economic growth with its carrying capacity and social inclusivity. The process of preparing a State Structure Plan following the manual of state structure plan stated in the PlanMalaysia 2020 Edition is to propose a new development idea and direction for Selangor State Structure Plan based on the current key of complex issues. The proposals and design of the selected district for the planning period between 2021 and 2035 are developed. The study was conducted as part of the Urban and Regional Planning student’s studio work, which consists of the plan’s process, stages followed by the situation and sectoral based analysis. The study proposed finger and linear development concepts, strategies, high-impact projects, implementation plans, and estimations of the cost of each major project. The proposed plan of the Selangor State Structure Plan 2035 promotes three (3) development thrusts, five (5) strategies, and twelve (12) high-impact projects for Selangor to thrive in its new development plan. The project provides experiential learning for the students as part of their training as future urban and regional planners.